Development of E-LKPD oriented minimum competency assessment (MCA) on 6C’s ability of high school students - Sugianto, Rahmad; Syaifuddin, Mohammad; Cholily, Yus Mochamad (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
Learning in the 21st century is currently required to be able to improve 6C’s skills (collaboration, communication, creative thinking, critical thinking, computing, and affection). This study aims to produce MCA-oriented E-LKPD products on 6C’s's abilities of high school students that are valid, practical and effective. The Research and Development research development method follows the four-D Model which consists of 4 stages of development, namely: define, design, develop, and disseminate. The research subjects were ten students of class XII at SMA Wachid Hasyim 2 Taman. Data collection techniques using questionnaires and post-tests. The data analysis used in this research is descriptive quantitative and qualitative analysis. The results of this study obtained the validity of the MCA-oriented E-LKPD on 6C’s abilities from validation data filled in by material experts, media experts and practitioner experts with a score of 3.3; 3.5; and 3.5. In addition, the practicality of the MCA-oriented E-LKPD on 6C’s abilities from the assessment of expert practitioners, namely teachers as users, gives a score of 3.5. While the effectiveness of the MCA-oriented E-LKPD on 6C’s abilities from the results of trials on small groups of ten students obtained an average of 81.13% with a very effective interpretation. Based on the results of this study, the developed E-LKPD media met the expected validity, practicality and effectiveness criteria. So that it can be said that the MCA-oriented E-LKPD products on the 6C’s abilities of high school students are valid, practical, and effective for use in learning